2020
DOI: 10.1108/ijebr-11-2019-0637
|View full text |Cite
|
Sign up to set email alerts
|

International assignments of employees and entrepreneurial intentions: the mediating role of human capital, social capital and career prospects

Abstract: PurposeDrawing on human capital (HC) and social capital (SC) as well as the Jack-of-all-trades theory, this paper aims to clarify the relationship between international assignments (IAs) of employees and their entrepreneurial intentions. The study proposes that such IAs provide specific environmental features which may enable employees to build up diverse skills and network relations conducive to entrepreneuship.Design/methodology/approachThe authors collected data using an online survey, targeting professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 130 publications
1
20
0
6
Order By: Relevance
“…Studies have shown that entrepreneurial motivations vary from country to country (Carsrud and Brännback, 2011; Hessels et al, 2008). Schlepphorst et al (2020) described intention as ambition influenced by a set of motivations, leading to actual behavior. Another study found that women entrepreneurs exhibited psychological characteristics like inventiveness, risk-taking, achievement motivation, problem-solving and determination, and that these constituted motivating factors for starting a business (Singh and Sengupta, 1985).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Studies have shown that entrepreneurial motivations vary from country to country (Carsrud and Brännback, 2011; Hessels et al, 2008). Schlepphorst et al (2020) described intention as ambition influenced by a set of motivations, leading to actual behavior. Another study found that women entrepreneurs exhibited psychological characteristics like inventiveness, risk-taking, achievement motivation, problem-solving and determination, and that these constituted motivating factors for starting a business (Singh and Sengupta, 1985).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…We argue that work experience abroad is linked to increases in a CEO's human capital. By staying abroad, (future) top managers accumulate valuable skills, knowledge and competencies (Carpenter et al 2001;Herrmann and Datta 2005;Jones 2013;Roth, 1995), which in turn helps them lead firms that operate abroad (Lu and Beamish 2001;Sambharya 1996) and enhances innovativeness, creativity or entrepreneurial orientation (Godart et al 2015;Maddux and Galinsky 2009;Maddux et al 2020;Schlepphorst et al 2020). In other words, international work experience is positively related to the development of the kind of human capital that is necessary to cope with the challenges in an increasingly globalized world (Gupta and Govindarajan 2002;Knight and Cavusgil 2004;Peng et al 2015).…”
Section: International Work Experience: the Human Capital Theory Perspectivementioning
confidence: 99%
“…According to (Ibrahim et al, 2021;Schlepphorst et al, 2020), when entrepreneurs use their social networks, their entrepreneurial performance will be uplifted because of the new prospects that the network introduces, which entrepreneurs would not be able to obtain within a short time to create a barrier to overcome the competition and business rivalries.…”
Section: Social Network and Entrepreneurial Performancementioning
confidence: 99%